A Study Investigating the Association of Dermatological and Infusion Reactions to Infliximab and Infliximab Trough Levels - Vivian Wai-Mei Huang; Neil Dhami; Darryl Fedorak; Connie Prosser; Carol Shalapay; Karen Ivy Kroeker; Brendan Phillip Halloran; Levinus Albert Dieleman; Richard Neil Fedorak (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Although infliximab is an effective therapy for inflammatory bowel disease (IBD), it is associated with dermatological events and infusion reactions. It is not known whether a relationship between these adverse events (AEs) and infliximab trough levels (ITLs) exists.